Design and Analysis of a Lab IP Spy Camera and Alarm System using Raspberry Pi and ATMEGA328P - Edozie, Enerst; Wantimba, Janat; Kalyankolo, Zaina; Adabara, Ibrahim; Ukagwu, Kelechi John (System, 2020)
Security is a very important thing to be concerned in our day-to-day life. Everyone wants to be secured as much as possible. Knowing our home or office is secure provides us peace of mind. With the increasing concern over better protection of people and assets, security departments are required to provide a higher level of security than before: proactive prevention, better situational awareness, earlier detection, quicker identification and prompter action. Now many organizations are continually reevaluating and enhancing their video surveillance to provide optimal daily security and operational efficiency. As the technology is advancing day by day, there are various alternatives occurring for the already present or previous technologies. Internet of Things (IOT) is an upcoming technology that makes use of Internet to control/monitor physical devices connected to the Internet. The basic premise is to have smart sensors collaborate directly without human involvement to deliver a new class of applications. IOT gives user the ability to control more than one digital thing easily through a comfortable Graphical User Interface (GUI) over the Internet. This paper aim to design an Embedded Real-Time Security System Based on Raspberry Pi for intruder observation that reinforces surveillance technology to provide essential security to the Lab equipment and associated control. And also to design a low cost Alarm system based on Microcontroller and ultrasonic sensor that takes proper measure to prevent intrusion, unwanted and unauthorized user(s) into the Lab. Ultrasonic sensor sense the presence of an intruder & Controller reads the signal from sensor, if intruder is detected, it turns on the buzzer. At the same time the live stream vide of the intruder can be monitored, and also the IP spy camera control system will send an image of the intruder via Gmail to the user. The designed system has been proven to be a reasonable advancement in access control and security system technology.
Keywords: IOT, Raspberry Pi, IP Camera, Microcontroller, Ultrasonic sensor, Gmail notification, Security.